The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.5380/rf.v50i4.65682
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus Inicial Growth on Humic Cambisol With Application of Limestone, Gypsum, and Lime Mud

Abstract: The high demand for forest products in Brazil estimates a 2 million hectares increase in reforestation areas over the next 10 years, highlighting Eucalyptus species. However, these crops usually occur in acid soils that need correction to achieve high productivity. Besides limestone, lime mud, a residue from the cellulose industry, and gypsum can also be used as correctives, but there are doubts about doses and ways of application with the best results. Thus, were evaluated the soil chemical attributes, foliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the experiment in question, however with assessments of DBH, height and estimated volume per hectare at 12, 15 and 24 months of cultivation age, Pfleger et al (2020) observed that for DAP and volume, at 12 months, the limestone applied at a lower dose on the surface in the planting strip (T3) had an increase, in relation to the control treatment (T1). At 15 months, the application of limestone on the surface in the planting strip (T3), and limestone and gypsum on the surface in the planting strip (T6), the DBH and volume increased in relation to the gypsum incorporated in the planting furrow (T9).…”
Section: Plant Developmentmentioning
confidence: 89%
See 1 more Smart Citation
“…In the experiment in question, however with assessments of DBH, height and estimated volume per hectare at 12, 15 and 24 months of cultivation age, Pfleger et al (2020) observed that for DAP and volume, at 12 months, the limestone applied at a lower dose on the surface in the planting strip (T3) had an increase, in relation to the control treatment (T1). At 15 months, the application of limestone on the surface in the planting strip (T3), and limestone and gypsum on the surface in the planting strip (T6), the DBH and volume increased in relation to the gypsum incorporated in the planting furrow (T9).…”
Section: Plant Developmentmentioning
confidence: 89%
“…The sources of Ca used in the experiment were dolomitic limestone (PRNT: 56% and moisture: 1%), agricultural gypsum (33% of Ca) and lime mud (PRNT: 87% and moisture: 30.5%) (PFLEGER et al, 2020). The materials gypsum, dolomitic limestone and lime mud used for the experiment were analyzed in an energy dispersion X-ray fluorescence spectrometer.…”
Section: Methodsmentioning
confidence: 99%